Effective schools - McInerney, D. M. 1948-; Dowson, Martin; Van Etten, Shawn (Research on sociocultural influences on motivation and learning ;, 2006)
Students arrive in our classrooms with complex sociocultural histories that include family, cultural, physical, social, emotional, and prior learning experiences. In order to be effective, schools must directly address these complex histories in meaningful, relevant and creative ways. The aim of this volume is to examine research on effective schooling from a sociocultural perspective - with a focus on developing the capacities of diverse students in diverse educational contexts. The chapters in this volume cover a wide range of important topics as listed below.